Effect of friction-welding parameters on the tensile strength of AA6063 with dissimilar joints (Fracture and Structural Integrity, 2022)
In this paper, the effect of welding parameters of rotary friction welding between AA6063 and AISI4130 and AA6063 and Copper are investigated. The major influencing parameters considered are upset pressure, friction time and friction pressure of friction welding are considered for this study. The Taguchi’s design of experiments was conducted for the influencing parameters and their levels. The tensile test experimentation was carried out and the results of the AA6063 and AISI4130 and AA6063 and Copper are compared. The ultimate tensile strength of AA6063-AISI4130 joint and AA6063-Copper joint was improved by increasing upset pressure up to 97MPa with FP of 71 MPa and FT of 4 sec. On the side of AA6063, intermetallic compounds have formed, as seen in SEM micrographs. Microcracks are forming on the side of AA6063 and propagates along the grain boundaries. The effect of the influencing parameters on the tensile strength of the dissimilar joints are studied using the Taguchi’s DOE and ANOVA. From the outcomes it is observed that the friction pressure influence more on the strength of the AA6063 dissimilar joints.
Keywords: AA6063; Copper; AISI4130; Friction welding; Taguchi’s DOE